Deconstruct to reconstruct: Is it possible to tax big data, e-commerce, and the digital economy? (2018)
The emergence of new business models such as app stores, online advertising, cloud computing, participative network platforms, high-speed trading, and online payment services has reshaped the global economy and made it difficult for tax authorities to determine what and where to tax. Technologies in the new digital economy make it possible for companies to operate in countries without any physical presence. While companies like Netflix, Google, and AirBnB provide services and earn profits in different countries, tax loopholes and intricate tax planning enables them to pay little to no taxes in many of these same countries. For example, Netflix earned more than US$100 billion in Colombia in 2016, but it did not pay any direct or indirect taxes in the country. The absence of a specific tax or legal rule that targets digital companies has prevented Colombian tax authorities from taxing companies like Netflix. This experience is similar to that of many tax authorities around the world. Therefore, this paper seeks to develop a modern benefit principle theory that will allow tax authorities to tax companies in the digital economy, assuring they pay taxes in the countries they operate in